Frequency of different histopathological types of esophageal cancer patients at oncology department of a tertiary care hospital in Karachi - Sheikh, Zoya; Haider, Ghulam; Ahmed, Khalil; Bhunisha, Dr. (Journal of Fatima Jinnah Medical University, 2021)
Background: Around the globe, carcinoma of the esophagus is the eighth most prevalent cancer with an incidence of 456,000 cases per year and is the sixth cause of cancer mortality. There are two major histological subtypes of carcinoma of the esophagus, esophageal squamous cell carcinoma and adenocarcinoma. The aim of the current study is to evaluate the frequency of different histopathological types of esophageal cancer in patients presenting at the tertiary care hospital of Karachi. Patients and methods: It was a cross-sectional study conducted at the Department of Clinical Oncology, Jinnah Postgraduate Medical Center, Karachi from March 2017 till March 2019. Two hundred and one histologically proven cases of esophageal cancer of in patients of either gender and between 15-80 years of age were included. Patients were interviewed and data regarding age, gender, education, marital status, employment status, addictions like cigarette or huqqa smoking, consumption of pan, betel nut, naswar, or gutka were recorded. Endoscopy and histology and computed tomography scan were performed. Stage, site, grade and type of tumor were noted. SPSS version 23 was used to analyze data. Mean and SD were calculated for quantitative variables. Frequency and percentage were calculated for qualitative variables. A Chi-square test was used to assess the significance between age and gender with type of EC. A p-value≤0.05 was taken as significant. Results: Mean age of the patients was 47.84. The majority of the patients had stage 2 of cancer (42.8%) and lower tumor site (62.2%) Squamous cell carcinoma was the most common histopathological type in 137 patients out of 201 (68%). The age, gender, smoking, consumption of pan, grade, site, and stage of the tumor showed a statistically significant difference when compared with esophageal squamous cell carcinoma and esophageal adenocarcinoma. Conclusion: The burden of esophageal squamous cell carcinoma is dramatically increasing in the Pakistani population and squamous cell carcinoma was the most common histopathological type.